The Effect of Oral Consumption of Honey- Saffron syrup with Date syrup on Labor Pain in Nulliparous Women - Hana Sohrabi; Roya Karimeh; Golbahar Ghaderkhani; Roonak Shahoei (Mashhad University of Medical Sciences, 2022)
Introduction: Labor pain is one of the most severe pains which a woman experiences during childbirth. Therefore, due to the importance of reducing labor pain and performing normal vaginal delivery, the present study was conducted aimed to compare the effect of oral consumption of honey-saffron syrup with date syrup on labor pain in nulliparous women.Methods: This randomized clinical trial study was performed in 2019 on 180 primiparous women referring to the maternity ward of Besat Hospital in Sanandaj. The subjects were randomly divided into three groups: honey saffron syrup, date syrup and placebo group. Inclusion criteria were: nulliparous women, 4 cm dilatation of the cervix, age 18-35 years, and singleton pregnancy. The above fluids were given at the beginning of the study (dilatation of 4 cm) and then every 30-60 minutes until the end of the active phase of the first stage of labor according to the patient's desire. Pain assessment line was used to evaluate the severity of labor pain. Data were analyzed using SPSS software (version 24) and analysis of variance, Chi-square and Repeated Measurement tests. P<0.05 was considered statistically significant.Results: There was no statistically significant difference between the three groups in terms of mean pain intensity at the beginning of the active phase before the intervention (P=0.690). After the intervention, there was a statistically significant difference between the three groups at the end of the active phase (P<0.001), the second stage (P<0.001) and the third stage of labor (P<0.001). Also, pain intensity in the second stage of labor was lower in the date syrup group compared to the honey-saffron syrup group (P=0.015. But, there was no statistically significant difference between the two intervention groups at the end of the active phase (P=0.928) and the third stage of labor (P=0.652).Conclusion: Consumption of honey-saffron syrup and date syrup are both effective in reducing labor pain, but date syrup in the second stage of labor is more effective than honey-saffron syrup and it can be used instead of drug interventions to reduce labor pain.